Geodynamic modeling of geoid changes and true polar migration in the geological past using spherical harmonic analysis - Tserklevych, A.L.; Badlo, T.B.; Shylo, Ye.O.; Volos , I.V.; Shchur, B.I. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2026)
The results of paleogeoid reconstruction for different Phanerozoic (0—540 million years) geological epochs using spherical harmonic analysis are presented. The method is based on an assumption of the relative stability of the relationship between topography and geoid over geological time for low- and medium-degree of spherical harmonics. The basis for this assumption is that most of the geoid topography (about 9/10) must originate from inhomogeneities in the distribution of subcrustal density, which are more stable in geological time. Knowing the modern relationship between topography and the geoid and having reconstructions of paleotopography, it is possible to estimate the ancient shape of the geoid by removing the contribution of the modern topography of the lithosphere to the heights of the geoid and reconstructing the geoid (paleogeoid) based on paleo-reconstructions of topography in past geological periods. We used modern models of the geoid EGM2008, topography ETOPO1, and paleotopographic reconstructions PaleoDEM. An algorithm is proposed that includes determining the transfer function between topography and geoid, removing the influence of modern topography, and restoring the paleogeoid based on reconstructed paleotopography. The modeling results demonstrate that the main contribution to the formation of the global geoid (about 90 %) is due the mantle density inhomogeneities to depths of ~1000 km, while the contribution of surface topography is secondary. Analysis of second-order harmonic coefficients allowed us to reconstruct the trajectory of the Earth’s rotational pole migration, with a maximum deviation of about 2600 m during the Phanerozoic. The results are consistent with current ideas about the dominant role of mantle convection in shaping the Earth’s global figure and confirm the connection between tectonic processes, mass redistribution, and changes in the planet’s inertia tensor.